Using Flashcard Media is Seen from the Result of the Skill in Writing Narrative Texts Fifth-Grade Elementary School Students - Ma'rifatul Khasanah; Sigit Yulianto (Jurnal Pendidikan Indonesia, 2024)
Writing skills cannot be acquired naturally, but must go through a continuous learning and practice process. Many students still need to bee narrative essays and are less able to develop words into sentences. This study aimed to determine the effectiveness of using flashcard media on narrative text writing skills for grade V. This study is an experimental study. The research design used was a quantitative experimental design with a non-equivalent group control pattern. This subject involved grade V students in two classes with 56 students. Data collection techniques in this study were carried out through documentation, observation, and tests. The data obtained were analyzed using descriptive analysis. Data analysis techniques used the t-test and n-gain (mean difference). The results showed that the use of flashcard media had a significant positive impact on improving the narrative text writing skills of grade V students. It was concluded that using flashcard media can improve grade V students' narrative text writing skills. These findings underline the importance of providing effective alternatives in the learning process.